Lingustic-cognitive approach to the analysis of intercultural communication - Sereda, A. (ХНУ ім. В. Н. Каразіна, 2017)
The given work is devoted to research of intercultural communication in the world of linguistic-cognitive paradigm. Such approach makes possible realization of complex analysis of communication taking into account factors, which causing its course, and revealing of its nationalspecific components. The discourse is considered as multidimensional linguistic-cognitive communicative integrity. In conditions of intercultural communication analysis of discursive activity of people opens features of thinking and verbal behaviour of carriers of different language cultures. Дана робота присвячена дослідженню міжкультурної комунікації в світі лінгвокогнітивної парадигми. Такий підхід дозволяє здійснювати комплексний аналіз комунікації з урахуванням факторів, що обумовлюють її протікання і виявляти її національно-специфічні складові. Дискурс при цьому розглядається як багатоаспектна лінгво-когнітивнокомунікативна цілісність. В умовах міжкультурної комунікації аналіз дискурсивної діяльності людей розкриває особливості мислення і вербальної поведінки носіїв різних мовних культур.
Лінгво-когнітивний підхід до аналізу міжкультурної комунікації
Keywords: intercultural communication; linguistic-cognitive paradigm; discourse